pengaruh leverage dan sales growth terhadap manajemen laba - Ruswardana, Benyamin (COMPETITIVE, 2023)
AbstractThe purpose of this research is to examine the effect of leverage and sales growth on earnings management. The population in this research the companies in the manufacturing sector basic industry and chemical on the Indonesia Stock Exchange during period 2018 to 2020. This research use the sampling data of 24 firms. The sampling is based on the method of purposive sampling. The research is a quantitative research using classic assumption test and multiple linear regressions analysis.The result of this research shows that proportion of leverage have no significant effect on earning management. While sales growth has a significant positive effect on earning management. Keywords:Leverage, Sales Growth, Earning Management